The Relationship of The Medication Adherence Model to The Quality of Life of Communities Pulmonary Tuberculosis Suffering in The Working Area of The Muliorejo Health Center, Sunggal District, Deli Serdang 2023 - Megawati, Megawati; Rinawati, RR.Sri Arini Winarti; Soep, Soep (Jurnal Keperawatan, 2024)
Tuberculosis sufferers experience changes in their physical, psychological health and social life which can have an impact on the quality of life of pulmonary tuberculosis sufferers. Curing pulmonary tuberculosis requires regular treatment for up to 6 months. The purpose of this research is to identify the relationship between the Medication Adherence Model and the Quality of Life of People Suffering from Pulmonary Tuberculosis at the Muliorejo Community Health Center, Sunggal District, Deli Serdang Regency. This research method uses descriptive collaborative with a cross sectional approach. Sampling was taken by accidental sampling with a sample size of 60 respondents. Medication adherence was obtained using the MMAS-8 questionnaire and quality of life using the WHO Qol-BREF questionnaire. The statistical analysis used is the Chi-Square test. Of the 60 respondents, 25 respondents were found in the low medication adherence category, namely 25 people (41.7%) had a poor quality of life, 20 people (33.3%) had a moderate quality of life and none had a moderate quality of life. good, out of a total of 30 respondents in the high medication adherence category, 35 people (58.3%) had a quality of life in the moderate category, 20 people (33.3%) experienced a quality of life in the good category and no one experienced a poor quality of life. Based on the results of the Chi-Square Test, it was found that the pvalue (0.000) was smaller than the significant value (0.05) so that Ha was accepted, which means there is a relationship between adherence to taking medication and the quality of life of Tuberculosis patients in the Muliorejo Community Health Center working area. There is a relationship between adherence to taking medication and quality of life in tuberculosis patients in the Muliorejo Community Health Center working area. Consume nutritious food · Let sunlight enter the room · Use a mask · Limit contact at the start of treatment · Wash your hands frequently.